2011
DOI: 10.1007/s00296-011-2039-z
|View full text |Cite
|
Sign up to set email alerts
|

Weak CD4+ T-cell responses to citrullinated vimentin in rheumatoid arthritis patients carrying HLA-DR9 alleles

Abstract: Citrullinated vimentin (cVIM) is one of the antigens specifically targeted by anti-citrullinated protein antibodies (ACPA) in rheumatoid arthritis (RA) patients. The association between ACPA and certain HLA-DRB1 alleles, those coding for the shared epitope (SE), suggests that this response could be T-cell mediated. HLA-DR9 alleles, which do not code for the SE, have recently been associated with ACPA (+) RA. The objective of this work was to study CD4+ T cell responses to cVIM in RA patients and healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
1
1
Order By: Relevance
“…In this study we selected and screened a number of citrullinated GRP78 peptides for binding to two HLA alleles, HLA-DR*0101 and HLA-DP*0401, other than HLA-DR*0401. Our previous work and others have also shown that citrullinated peptides have affinity for other non-SE alleles and we again confirm this showing CD4 T cell responses to citrullinated GRP78 peptides in HHDII/DP4 transgenic mice ( 18 , 24 , 25 ). Immune response analysis in HLA transgenic mice identified one peptide (aa189-208) that stimulated IFNγ responses across two HLA alleles, HLA-DP*0401 and HLA-DR*0101 and this was shown to cross react with a peptide spanning aa187-206.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we selected and screened a number of citrullinated GRP78 peptides for binding to two HLA alleles, HLA-DR*0101 and HLA-DP*0401, other than HLA-DR*0401. Our previous work and others have also shown that citrullinated peptides have affinity for other non-SE alleles and we again confirm this showing CD4 T cell responses to citrullinated GRP78 peptides in HHDII/DP4 transgenic mice ( 18 , 24 , 25 ). Immune response analysis in HLA transgenic mice identified one peptide (aa189-208) that stimulated IFNγ responses across two HLA alleles, HLA-DP*0401 and HLA-DR*0101 and this was shown to cross react with a peptide spanning aa187-206.…”
Section: Discussionsupporting
confidence: 90%
“…RA is associated with the shared epitope SE haplotypes and leading investigators to initially conclude that only these HLA molecules can present citrullinated epitopes ( 23 ). In contrast we and others have shown that alleles without the SE motif can present citrullinated epitopes ( 18 , 24 , 25 ) which is more in line with their role of recognising stressed cells in any individual. There is evidence that SE alleles may bind some citrullinated epitopes with higher affinity ( 26 , 27 ) resulting in more aggressive activation of CD4 T cells which when accompanied by joint erosion, antibodies and inflammation can lead to RA.…”
Section: Introductioncontrasting
confidence: 46%
“…Although the precise aetiology remains to be established, it is thought that RA results from a breach in immune tolerance. T cell responses to several (joint‐associated) autoantigens, including ‘altered self’ citrullinated peptides, can be detected in a proportion of RA patients , and the function of peripheral blood regulatory T cells (T regs ) is impaired in RA patients with active disease . Immunosuppressive drugs (including biological drugs) can relieve disease symptoms effectively, but none of the currently available treatments provide a cure, i.e.…”
Section: Introductionmentioning
confidence: 99%